2013
DOI: 10.1120/jacmp.v14i5.4622
|View full text |Cite
|
Sign up to set email alerts
|

The future of medical physics in the US health‐care system

Abstract: This issue, I would like to digress from the meaning of the JACMP and discuss with you some personal thoughts on the US health-care system and the future of medical physics under the Affordable Care Act. My credentials for discussing this topic include a newly minted PhD in Health Management from the School of Public Health at the University of Louisville. I spent many rewarding hours in classes, seminars, and lectures learning about the changes in US health care and public health over the past 11 years. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Krayenbuehi et al also reported a similar study in six MPM patients with significant postoperative intrathoracic air cavities. They concluded that VMAT allowed a lower lung dose and was less affected by air cavity variation than IMRT [ 20 ]. Helical tomotherapy is a rotational delivery method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krayenbuehi et al also reported a similar study in six MPM patients with significant postoperative intrathoracic air cavities. They concluded that VMAT allowed a lower lung dose and was less affected by air cavity variation than IMRT [ 20 ]. Helical tomotherapy is a rotational delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher percentages of the contralateral lung volume receiving ≥5 Gy (V5), or the mean lung dose (MLD), have been associated with severe pulmonary toxicity [ 15 18 ]. Volumetric modulated arc therapy (VMAT), a form of intensity-modulated arc therapy, is a promising new method using the regular linear accelerator and, compared with conventional static IMRT, it has the potential to improve target coverage and dose sparing to the organs at risk (OARs) [ 19 , 20 ]. However, there are limited reports of VMAT.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, only 1 study has addressed this issue reporting a rate of acute Grade 3 pneumonitis in 20% of patients, a figure that favorably matches with previously reported data on IMRT. 54 , 55 …”
Section: Resultsmentioning
confidence: 99%
“…Thompson [ 19 ] also report difficulties in the identification of a magnetic valve in a CT image. The manual identification is not a practical procedure to be employed in the routine of a radiotherapy service, and another possible procedure could be minimizing artifacts using post-reconstruction algorithms [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%